THE REASONABLENESS OF USING DRUGS TO TREAT PNEUMONIA (Vietnam Journal of Community Medicine, 2021)
Objective: To investigate the reasonableness of using drugs to treat pneumonia at Can Tho Children’s Hospital. Subjects and methods: a retrospective-descriptive study on 384 inpatient medical records at Can Tho Children’s Hospital from January 2019 to December 2019 was diagnosed pneumonia. Results: The percentage of the initial treatment regimen that was not reasonable with the recommended antibiotic regimen was relatively high at 84.11%. The proportion of antibiotics with inappropriate dose was only 1.71% of the total number of surveyed cases. The appropriate rate of antibiotic dose was 98.29%. The proportion of adjuvants with high appropriate doses such as Salbutamol, Hydrocortison and Prednisolon accounted for 100%. The rate of taking antibiotics in accordance with recommendations accounted for 94.67%. The rate of adjuvanvt drug delivery was very high, there were only a few cases that did not comply with recommendations such as Ibuprofen with 14 cases, accounting for 37.84%, Acetylcysteine ​​and Hydrocortison accounted for 14.58% with 7 cases, and Prednisolon and Budesonid accounted for the very low percentage. Conclusion: The proportion of the initial treatment regimen that was not compatible with the antibiotic regimen was relatively high. The appropriate rate of antibiotic dose was high. The proportion of adjuvants with suitable doses was high such as Salbutamol, Hydrocortison and Prednisolon. The antibiotic delivery rate was consistent with recommendations. The rate of adjuvant delivery was very high.
Keywords: Rational use of drugs, Pneumonia